Three leading suicide methods in the United States, 2017–2019: Associations with decedents' demographic and clinical characteristics - Choi, Namkee G.; Marti, C. Nathan; Choi, Bryan Y. (Frontiers in Public Health, 2022)
Background and aims The U.S. suicide data show that use of lethal methods, specifically firearms and hanging/suffocation, has been increasing among young and middle-aged adults of both sexes over the past decades. In this study, we examined demographic and clinical correlates of use of firearms, hanging/suffocation, and poisoning as suicide methods among suicide decedents age 18+. Methods Data came from the 2017-2019 National Violent Death Reporting System (NVDRS; N = 94,454, age ≥ 18 at the time of suicide; 74,042 men and 20,412 women). We fit generalized linear models (GLMs) for a Poisson distribution with a log link to examine (1) changes in four suicide methods (firearms, hanging/suffocation, poisoning, and other) during the study period, controlling for sex and age group; and (2) correlates of firearms, hanging/suffocation, and poisoning use. Results In all age groups, 55% of men and 30% of women used firearms; 28% of men and 29% of women hanging/suffocation; 9% of men and 32% of women poisoning, and 8% of men and 9% of women “other” methods. Men age < 45 had higher likelihood of firearm and/or hanging/suffocation use than those age 45–64. Women age<45 also had higher likelihood of hanging/suffocation than those age 45–64. Prior suicide attempt history was associated with higher likelihood of poisoning in both sexes and hanging/suffocation in men; mental disorders/SUD were associated with higher likelihood of hanging/suffocation and poisoning in both sexes; physical health problems were associated with higher likelihood poisoning in both sexes and firearm use in men; relationship problems were associated with higher likelihood of firearm use; legal problems and job/financial/housing problems were associated with higher likelihood of hanging/suffocation in both sexes; and more crises were associated with higher likelihood of firearm use in both sexes. Implications The findings call for the following suicide prevention strategies: (1) restricted access to firearms; (2) improved access to mental health/substance use treatment; (3) improved long-term and palliative care services for those (mostly older adults) with physical health problems; (4) financial/housing support policies to mitigate economic hardship; and (5) more research to identify effective strategies to curtail the increasing use of firearm and hanging/suffocation among young and middle-aged adults.